2020
DOI: 10.1155/2020/4213807
|View full text |Cite
|
Sign up to set email alerts
|

Role of Erythromycin-Regulated Histone Deacetylase-2 in Benign Tracheal Stenosis

Abstract: Objective. This study aims to explore the role of erythromycin-regulated histone deacetylase-2 in benign tracheal stenosis. Methods. The rabbit model of tracheal stenosis was established. The rabbits were randomly divided into 8 groups. Histone deacetylase-2 (HDAC2) expression was detected by immunofluorescence. The expression of type I collagen and type III collagen was detected by immunohistochemical method. The expression of TGF-β1, VEGF and IL-8 in serum and alveolar lavage fluid was detected by ELISA. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…Tracheal stenosis (TS) is an uncommon disease caused by repeated injury and repair of the tracheal mucosa and hyperplasia of the resultant granulation tissue. 1 TS is a chronic inflammatory process that can result from several possible etiologies, where the most common being long-term mechanical ventilation with endotracheal intubation. Myriad additional etiologies can also result in luminal compromise of the proximal airway including neck trauma, tracheotomy, infection (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Tracheal stenosis (TS) is an uncommon disease caused by repeated injury and repair of the tracheal mucosa and hyperplasia of the resultant granulation tissue. 1 TS is a chronic inflammatory process that can result from several possible etiologies, where the most common being long-term mechanical ventilation with endotracheal intubation. Myriad additional etiologies can also result in luminal compromise of the proximal airway including neck trauma, tracheotomy, infection (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that tracheal transplantation has been considered a viable option for the reconstruction of long tracheal defects, 9 while tissue engineering tracheal graft implantation may be the last chance for patients with severe cicatricial stenosis 8 . At the same time, local and systemic anti‐infection has also been found to be effective for TS, but most of the data are related to animal models 42–44 . The specific indicators of the clinical patients in this research fully demonstrated that comprehensive treatment, including bronchial intervention and systemic anti‐infection, could greatly improve various indicators of TS patients.…”
Section: Discussionmentioning
confidence: 73%
“…HATs acetylate histones, which result in chromatin unwinding at specific sites, thereby increase the binding of transcription factors and RNA polymerase to DNA and promote inflammatory gene transcription, while HDACs remove the acetyl groups from the histone tails and inhibit the transcription of inflammatory genes ( 30 , 31 ). Endotracheal intubation or tracheotomy may cause an airway inflammatory response that is associated with changes in HDAC (mainly HDAC2) activity ( 19 , 32 ). Distinct subtypes of HDACs catalyze different patterns of deacetylation and regulate different genes, thereby generating different effects ( 33 ).…”
Section: Discussionmentioning
confidence: 99%